Managing outbreaks of invasive species – A new method to prioritize preemptive quarantine efforts across large geographic regions. (1st March 2015) - Withrow, J.R.; Smith, E.L.; Koch, F.H.; Yemshanov, D.
Abstract: In pest risk assessment it is frequently necessary to make time-critical decisions regarding management of expanding pest populations. When an invasive pest outbreak is expanding rapidly, preemptive quarantine of areas that are under imminent threat of infestation is one of only a few available management tools that can be implemented quickly to help control the expansion. The preemptive quarantine of locations that surround an infested area also acts as a safeguard to counteract the risk of failed detections of the pest in field surveys. In this paper, we present a method that assesses the suitability of preemptive quarantine measures at the level of small geographical subdivisions (U.S. counties). The cost of a preemptive quarantine in a given county is weighed against the protective benefit of delaying the spread of an outbreak to other neighboring counties. We demonstrate the approach with a decision support model that estimates the suitability of preemptive quarantine across multiple counties that surround areas infested with the emerald ash borer (Agrilus planipennis Fairmaire (EAB), Coleoptera: Buprestidae), an emerging major threat to ash tree species ( Fraxinus spp.) in North America. The model identifies the U.S. counties where the installation of preemptive quarantine would most effectively slow the spread of EAB populations and reduce risk to high-value areas. Highlights: A model estimates suitability of preemptive quarantine for a set of U.S. counties. The results assisted in directing sampling efforts of emerald ash borer in 2012. The model gives insight into the interplay of ecology, geography, and management. Results are sensitive to invasion amplitude and quarantine efficacy. Results are also sensitive to the location of high-value host.